Perancangan Inverter Dual Conversion Push Pull-Full Bridge pada Aplikasi Fotovoltaik - Ariwibowo, Cahyo; Warsito, Agung; Karnoto, Karnoto (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Currently, electric energy is essential for human needs, while for remote areas not all of them powered from PLN. The solution is to use existing energy and transforms it into electrical energy. One of the energy that can be considered is solar energy.Photovoltaic is a device that directly converts solar energy into electricity. To be more efficient, electricity from photovoltaic stored in batteries that can be used at any time during overcast conditions or at night when sunlight does not exist. Most electrical appliances use a standard 220 Volt AC voltage and frequency of 50 Hz, while the electricity generated by photovoltaic is a DC voltage. To get electricity as specified electrical equipment, inverter is used. Inverter is a power electronic device that converts DC voltage into AC voltage.Inverter that was designed can be burdened with incandescent lamp between 100-300 watt with an average efficiency of 63%. Photovoltaic water pump system can supplying 1440 liters of water for every 1 cycle of charging a 65 Ah battery for 52 minutes 18 seconds with an average efficiency of 61%.Â Keyword :Â Â solar energy, photovoltaic, battery, inverter, water pump